2021
DOI: 10.1111/anae.15421
|View full text |Cite
|
Sign up to set email alerts
|

An update on the management of chronic pelvic pain in women

Abstract: Summary Chronic pelvic pain represents a major public health problem for women and impacts significantly on their quality of life. Yet it is under‐researched and a challenge to manage. Women who suffer from chronic pelvic pain frequently describe their healthcare journey as long, via a variety of specialists and frustrating, with their pain often dismissed. Aetiological factors and associations are best conceptualised using the ‘three P’s’ model of predisposing, precipitating and perpetuating factors. This int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 52 publications
0
22
0
1
Order By: Relevance
“…Lifestyle factors such as physical inactivity, stress, poor sleep, unhealthy diet and smoking are associated with chronic pain severity and sustainment, and lifestyle changes have a positive impact on chronic pain 198 . Although there is no specific evidence of these data and benefits in women with vulvodynia, lifestyle advice could be part of the multidimensional approach 151 …”
Section: Clinical Featuresmentioning
confidence: 99%
“…Lifestyle factors such as physical inactivity, stress, poor sleep, unhealthy diet and smoking are associated with chronic pain severity and sustainment, and lifestyle changes have a positive impact on chronic pain 198 . Although there is no specific evidence of these data and benefits in women with vulvodynia, lifestyle advice could be part of the multidimensional approach 151 …”
Section: Clinical Featuresmentioning
confidence: 99%
“…These have been shown to improve dysmenorrhoea, pelvic pain, dyspareunia and improve quality of life. COC pills can reduce the recurrence of endometrial lesions (Grandi et al., 2019; Vincent and Evans, 2021). Gonadotrophin-releasing agonists with low-dose hormone replacement therapy may give benefit after 3 months of therapy (Vincent and Evans, 2021).…”
Section: Possible Causes Of Painmentioning
confidence: 99%
“…COC pills can reduce the recurrence of endometrial lesions (Grandi et al., 2019; Vincent and Evans, 2021). Gonadotrophin-releasing agonists with low-dose hormone replacement therapy may give benefit after 3 months of therapy (Vincent and Evans, 2021). Interestingly, some research has suggested that women who ate more than two servings of red meat a day were 56% more likely to have endometriosis in comparison with those who did not.…”
Section: Possible Causes Of Painmentioning
confidence: 99%
See 2 more Smart Citations